Cooperative Energy Broadcasting System With Massive MIMO - Zhao, Long; Zheng, Kan (IEEE communications letters, 2016)
Different from information transmission, inter-cell interference benefits energy harvesting of energy users (EUs) in multi-cell scenario. Therefore, the objective of this letter is to maximize the average energy harvesting utility of multiple EUs by leveraging inter-cell cooperation. Considering channel state information (CSI) delay, a cooperative energy precoder with centralized implementation is first proposed when the energy stations (ESs) employ massive multiple-input multiple-output. Then, its distributed implementation is presented in terms of a local constraint at each ES and information exchange among ESs. Results indicate that the cooperative energy transfer significantly outperforms the non-cooperative energy transfer with either perfect or delay CSI, and the proposed energy precoder with proportional fairness utility can balance the harvested energy and fairness among different EUs.